Building a Low‐Cost, Internet‐of‐Things, Real‐Time Groundwater Level Monitoring Network. Issue 4 (25th August 2020) - Drage, John; Kennedy, Gavin
Abstract: A community‐based, real‐time, groundwater level monitoring network consisting of 11 sites was built in Nova Scotia, Canada, using privately owned domestic wells and low‐cost, custom‐made water level meters. The real‐time meters use an ultrasonic sensor to measure water levels and an Internet‐of‐Things device to transmit the data to the Internet by WiFi or cellular connection. The water level data are plotted in real‐time on a time‐series graph and are available immediately for online viewing and downloading. Based on observations at three sites, the real‐time water level meter data compare well to pressure transducer measurements, with mean absolute errors of less than 0.02 m. The meters are simple to build, and components are readily available from online suppliers at low cost.